2020
DOI: 10.1186/s12889-020-08883-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between morbidity of non-communicable disease and employment status: a comparison between Korea and the United States

Abstract: Background: Globally, the prevalence of chronic disease continues to rise and is likely to grow further over the coming decades due to population ageing. Since older age is associated closely with development of chronic disease, it stands to reason that demographic changes will increase the proportion of older workers with chronic disease. The aim of the present study was to determine how chronic diseases affect employment status in Korea and the USA. Methods: The study was based on National Health and Nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…A study in Spain found a 1.3-fold increased risk of hypertension and 1.5-fold increased risk of obesity in long-term unemployed men and women, respectively [19]. However, this association may be partially explained by the possibility that poor health could result in unemployment, instead of the reverse [4 ▪ ,20].…”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…A study in Spain found a 1.3-fold increased risk of hypertension and 1.5-fold increased risk of obesity in long-term unemployed men and women, respectively [19]. However, this association may be partially explained by the possibility that poor health could result in unemployment, instead of the reverse [4 ▪ ,20].…”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…This study showed a high prevalence of NCDs in Brazil, where almost half of the population reported having at least one disease, which reflects a challenge for the health system and for the economy, considering that these diseases are responsible for most of the expenses for both treatment and prevention 14 . The prevalence and burden of NCD are the highest in several countries [15][16][17] .…”
Section: Discussionmentioning
confidence: 81%
“…Metabolic disorders are non-communicable diseases with an increasing prevalence over the years; they entail considerably high healthcare costs in terms of prevention and treatment [ 1 ]. Their risk factors include unhealthy eating patterns, obesity, lack of physical activity, and alcohol and tobacco consumption [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%